2001
DOI: 10.1002/1521-3757(20010216)113:4<762::aid-ange7620>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A New, Efficient Route to Titanium-Silsesquioxane Epoxidation Catalysts Developed by Using High-Speed Experimentation Techniques

Abstract: Titanium centers dispersed on, and supported by, various forms of silica are catalysts with remarkable properties for partial oxidations. [1] The character of the active site varies with the silica support used. Although it has been established that in the best (on the basis of activity per gram of titanium) heterogeneous catalysts the Ti centers are all four-coordinate, [2±4] it is still unclear whether, for optimum performance, the active catalytic species requires the specific configuration of four siloxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The high‐speed experimentation screening: Silsesquioxane precursors for titanium catalysts were synthesised by the hydrolytic condensation of six different trichlorosilanes (R = cyclohexyl, cyclopentyl, phenyl, methyl, ethyl, and tert ‐butyl) in three highly polar solvents (dimethyl sulfoxide (DMSO), water and formamide) by means of high‐speed experimentation techniques. Previous work showed that the R group on the organosilane and the solvent in which the hydrolytic condensation is carried out are the most relevant parameters influencing the synthesis of silsesquioxanes 8. 11 The parameter space studied was defined by the full‐factorial combination of the six trichlorosilanes and the three solvents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The high‐speed experimentation screening: Silsesquioxane precursors for titanium catalysts were synthesised by the hydrolytic condensation of six different trichlorosilanes (R = cyclohexyl, cyclopentyl, phenyl, methyl, ethyl, and tert ‐butyl) in three highly polar solvents (dimethyl sulfoxide (DMSO), water and formamide) by means of high‐speed experimentation techniques. Previous work showed that the R group on the organosilane and the solvent in which the hydrolytic condensation is carried out are the most relevant parameters influencing the synthesis of silsesquioxanes 8. 11 The parameter space studied was defined by the full‐factorial combination of the six trichlorosilanes and the three solvents.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter space was screened as a function of the activity of the catalysts obtained after coordination of [Ti(OBu) 4 ] to the silsesquioxane structures in the epoxidation of 1‐octene with tert ‐butyl hydroperoxide (TBHP) 12. In Figure 1, the relative activities of the titanium silsesquioxanes are shown together with those of the titanium silsesquioxanes obtained from silsesquioxanes synthesised in acetonitrile, which gave the best results among the solvents tested in previous work 8. 9 The values are normalised to the activity of the most active titanium silsesquioxane found so far, specifically that obtained by reacting [Ti(OBu) 4 ] with cyclopentyl silsesquioxane a 7 b 3 [( c ‐C 5 H 9 ) 7 Si 7 O 12 TiOC 4 H 9 ] 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to the formation of metal‐containing silsesquioxanes (M‐POSS), which are relevant as building blocks for multifunctional composite materials or as model systems for heterogeneous catalysts 47. M‐POSS compounds, for example, have been dispersed on different silicas and polymeric matrices for the preparation of active catalysts in epoxidation,89 polymerization,10–11 and oxidative dehydrogenation of olefins 1215…”
Section: Introductionmentioning
confidence: 99%